Study of Relationship of Behavioural Pattern and Level of Aspiration, Home Environment, Emotional Intelligence of Kannada and English medium Secondary School Students: A Comparative Study of Schooling Mediums and their Impact on Students' Behaviour and Aspirations in Karnataka (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education is basis of every human’s life. Education enhances and grows ones personality in a beautiful manner. To be educated is to be civilized. At the National level we see that English medium schools are the most popular on the contrary the situation at the state level is different in the state of Karnataka especially people are more inclined towards schools with kannada medium.